Cabo Verde’s Poaceae Flora: A Reservoir of Crop Wild Relatives Diversity for Crop Improvement - Rocha, Vanézia (2021)
Africa is home to important centers of origin and diversity of crop wild relatives (CWR), including many species adapted to adverse agroecological conditions, namely drought and poor soils. Plant genetic resources from Cabo Verde Islands have been poorly explored for their potential to supplement the genetic pool of cultivated species. In this paper we identify Cabo Verde's CWR from the Poaceae family and provide a checklist of priority CWR taxa, highlighting those of particular conservation concern and the areas which should be the focus of the most intensive conservation efforts in these islands. Our results revealed that Cabo Verde archipelago is an important center of CWR diversity of West African crop millets, namely fonio (e.g., white fonio, Digitaria exilis, and black fonio, Digitaria iburua) and other African millets [e.g., pearl millet (Cenchrus americanus = Pennisetum glaucum), teff millet (Eragrostis tef), finger millet (Eleusine coracana), barnyard millet (Echinochloa colona), proso millet (Panicum miliaceum), and foxtail millet (Setaria italica)], which represent a diverse group of cereal crops, and important components in agriculture and food security of this country. Also, hotspot areas of diversity for in situ conservation were identified in Cabo Verde, as well as several populations occurring under extreme habitats conditions that are well adapted to drylands and poor soils. The evaluation of their potential for new ecologically important adaptive characteristics associated with tolerance to abiotic stresses is discussed. The survey of international Germplasm Banks revealed that very few accessions from Cabo Verde are conserved, contributing to the loss of genetic diversity of plant genetic resources in this archipelago. Particularly, the diversity of millets and the associated indigenous knowledge are critical for the food security and cultural identity of many poor farmers in Cabo Verde.